2022
DOI: 10.3389/fnut.2022.876620
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Combined With a Low-Carbohydrate Dietary Pattern in the Treatment of Overweight Polycystic Ovary Syndrome Patients

Abstract: ObjectivesTo determine the therapeutic effect of a Mediterranean diet (MED) combined with a low-carbohydrate (LC) dietary model in overweight polycystic ovary syndrome (PCOS) patients.MethodsIn this 12-week randomized controlled clinical trial, 72 overweight patients with PCOS were randomly assigned to one of two energy-restricted dietary models: the MED/LC diet or the Low fat (LF) diet. After the intervention, the number of the two groups returned to normal menstruation was counted. Body weight, body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 42 publications
0
27
0
2
Order By: Relevance
“…Calorie-restricted diets may be the best option for reducing IR and improving body composition [ 146 ]. Studies have shown that the Mediterranean diet—which emphasizes a high intake of vegetables, fruits, seafood, legumes, and nuts; whole grains as staple foods; and the promotion of vegetable oils—combined with a low-carbohydrate regimen improves endocrine disorders and menstrual cycles in overweight patients with PCOS [ 147 ]. International evidence-based guidelines recommend that all women with PCOS, especially those who are overweight or obese, engage in at least 150 min of aerobic exercise per week, including more than 90 min of vigorous exercise [ 148 ].…”
Section: Treatment Of Insulin Resistance In Polycystic Ovary Syndromementioning
confidence: 99%
“…Calorie-restricted diets may be the best option for reducing IR and improving body composition [ 146 ]. Studies have shown that the Mediterranean diet—which emphasizes a high intake of vegetables, fruits, seafood, legumes, and nuts; whole grains as staple foods; and the promotion of vegetable oils—combined with a low-carbohydrate regimen improves endocrine disorders and menstrual cycles in overweight patients with PCOS [ 147 ]. International evidence-based guidelines recommend that all women with PCOS, especially those who are overweight or obese, engage in at least 150 min of aerobic exercise per week, including more than 90 min of vigorous exercise [ 148 ].…”
Section: Treatment Of Insulin Resistance In Polycystic Ovary Syndromementioning
confidence: 99%
“…Regarding dietary changes, studies have shown that the MED (Mediterranean Diet)/LC (Low Carbohydrate Diet) diet model is a good treatment for overweight PCOS patients. MED)/LC promotes menstrual cycle regulation, affects weight, and its overall efficacy is significantly better than the LF (low-fat diet) diet [8].…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…Patients with PCOS who suffer from obesity develop insulin resistance (IR), which in this case is manifested as a result of a decrease in the immune response to circulating insulin [3]. Summarizing all the studies, several mechanisms of IR formation in patients with PCOS can be distinguished: genetic predisposition, violation of insulin secretion by beta cells of the pancreas, peripheral insulin resistance caused by the action of androgens on skeletal muscles, violation of insulin metabolism in the liver, serine phosphorylation of the insulin receptor, and others disturbance in the way of insulin signal transduction into the cell.…”
Section: Introductionmentioning
confidence: 99%